Transformation of Mad’u Mentality in Addressing Social Media Addiction: A Social Learning Theory Approach in the Psychology of Da’wah - Herawati; Maskanah; Dadang; Sukirman; Meity Suryandari (Journal of Education and Learning Sciences, 2026)
The rapid growth of digital technology has significantly transformed human behavior, including the mentality of mad’u in responding to social media use. However, excessive use has led to social media addiction, which negatively affects psychological, social, and spiritual aspects. This study aims to analyze how the mentality of mad’u transforms in dealing with social media addiction through the perspective of Social Learning Theory in da’wah psychology. The research applies a qualitative approach using library research, by examining relevant scholarly literature related to social media addiction, social learning processes, and Islamic da’wah strategies. The findings indicate that mad’u’s mentality is shaped through observational learning, imitation, and reinforcement from digital environments, especially through influencers and online communities. This condition requires adaptive and psychologically grounded da’wah strategies. The study concludes that integrating Social Learning Theory into da’wah practices can effectively transform mad’u’s mentality toward more critical, balanced, and spiritually grounded behavior in the digital era.